A PILOT TO IMPROVE GERIATRIC CARE QUALITY IN RURAL FLORIDA. (11th November 2018) - Hyer, K; Maynard, A
Abstract: Rural Americans are at increased risk for health disparities and older adults often carry additional burdens relevant to a higher incidence of comorbidities, cognitive decline, disability, and limited incomes. Increased vulnerability requires providers to monitor ongoing health issues carefully. Annual Medicare visits present an opportunity for primary care practices to assess multifactorial indicators of health, update prevention plans and to identify unique needs within rural settings. Our USF GWEP pilot deploys DNP students from the College of Nursing to collaborate with a rural primary care practice to enhance older adults' care. DNPs redesign protocols and workflow to improve adherence to annual Medicare visit, document advanced directives, and support care management planning. Findings include project charter and timelines, baseline quality measures, process workflow redesign and community resource referral where applicable.